Failure mode analysis of Austria's first road-integrated photovoltaic system - Erber Alexander; Grasel Bernhard (EPJ Photovoltaics, 2024)
The exploration of traffic areas as a novel photovoltaic integration opportunity within the traffic sector, specifically in road surfaces, has been demonstrated in various projects. Limited data and publications about the performance and failure modes of these innovative road-integrated modules highlights the need for a comprehensive failure analysis. This study focuses on first time assessing failure modes of road-integrated photovoltaic modules installed at Austria's first road-integrated PV system in Teesdorf. A comprehensive failure mode analysis is conducted at the 100 m2 PV parking place using a combination of quantitative and qualitative methods. These methods include regular visual inspections, I-V-curve measurements at both string- and module-levels (with a simplified STC correction), electroluminescence- and dark-I-V-curve measurements, and the use of monitoring data. The PV parking place produced 10.2 MWh in its first operation year, 27.18% less than the estimated yield. Visual inspections reveal various failure modes, including detachment of the module top layer, delamination, and broken module edges. In the analysed monitoring data continuous power losses are observed over the systems operation time. String-level power losses of up to 47.8% (mean: 33.5%) are calculated for the first year of operation. For the second year of operation the power losses reach a up to of 77.5% (mean: 56.2%). Cell cracks as the main cause of these power losses, attributed to vehicle loads, are identified through electroluminescence images. Out of 16 analysed strings with dark I-V-curve measurements three showed at least one bypass diode malfunctions. The combination of quantitative and qualitative methods identified multiple failure modes and their main causes. As a conclusion, the study highlights the challenges of integrating PV modules into road surfaces, emphasizing the need for standardisation and quality assurance in the field of road-integrated PV applications.